Niedoceniony potencjał czy przecenione możliwości dyplomacji kulturalnej? - Umińska-Woroniecka, Anna (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2016)
The article analyses the concept of soft power an cultural diplomacy from the theoretical point of view and in terms of practical state policies, where Poland is treated as a case study. The first part includes conceptualizations of cultural diplomacy as a soft power tool. It also discusses its role as an instrument of foreign policy. Next part discusses historical policy which refers to the society’s collective memory. The article presents recent Polish experiences in the area of state promotion through national culture in the context of the new Law and Justice Party government with special regard to the Ministry of Foreign Affairs.
Keywords: cultural diplomacy; cultural foreign policy; culture promotion abroad; public diplomacy; historical policy; soft power; Poland’s image abroad; stereotypes; instrumentalization of culture; foreign policy; national interest